Impact of the “health play” model in healthy life styles of primary school students - Álvarez Bogantes, Carlos (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2012)
Objective: The purpose of th is article was to evaluate the impact of a room interdisciplinary health behavior intervention in diet y physical activity among children in grade 4. Study design: A cuasi-esperimental field trial, with a 1 intervention conducted from February 15  through May 31. Subjects: 27 boys y 32 girls with a 9.2 age mean, took part in the study. The intervention, taught by regular teacher, computer teacher, family education teacher y by the coordinator of the intervention the physical education teacher, provided the experimental group a nutrition y physical education health program called “From playing to health. Results: Children in the intervention group had a significantly greater health knowledge, y a self-reported physical activity (P